APPLICATION OF DIGITAL MARKETING AS A MARKETING STRATEGY IN SYNTAX CORPORATION INDONESIA - Aldo Faisal Umam (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
The digital world is predicted to be a crucial point for all human activities, including business activities. This can be seen from several indicators in the form of increasing digital advertising expenditures, increasing ownership of smartphones to access the internet, improvements to telecommunications infrastructure in order to improve the quality of data access, as well as the launch of 4G services. Advances in internet technology that offer opportunities for the digital world with new interactions and market places , and even an unlimited network marketing world of business have made companies start paying attention to the importance of marketing their products or services using the internet. Based on the formulation of the problem above, the purpose of this study is: "To determine the effect of implementing digital marketing as a marketing strategy in Syntax Corporation Indonesia ". This study uses a descriptive method with a qualitative approach because the implementation includes data, analysis and interpretation of the meaning and data obtained. The results show that the implementation of digital marktring in Syntac has been going well, in terms of turnover and from all marketing channels, 70% of marketing platforms have been used.